Gaol, Winarty Olivia Br Lumban PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, KOMISARIS INDEPENDEN, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Br. Lumban Gaol, Winarty Olivia; Ni Luh Gede Erni Sulindawati (Vokasi : Jurnal Riset Akuntansi, 2024)
This study aims to analyze the effect of Corporate Social Responsibility disclosure, Independent Commissioners, Managerial Ownership, on Company Value in coal sub sector companies in 2020-2022. This type of research is quantitative research using secondary data obtained through the the company’s annual financial statements. The population of this study is the coal sub sector companies listed on the Indonesia Stock Exchange, using a purposive sampling method to determine the sample. Samples that meet the criteria is 14 companies with a total of three years of observation, namely 2020-2022, so the number of samples obtained is 42. The data analysis technique is multiple linear regression analysis using SPSS 23.0 for windows. The results show that corporate social responsibility has a positive but not significant effect on company value, independent commissioners has positive but no significant effect on company value, managerial ownership has a positive and significant effect on company value. And corporate social responsibility, independent commissioners and managerial ownership has a simultaneously effect on company value.